Ethical dimensions of translational developmental neuroscience research in autism - Manzini, A; Jones, EJH; Charman, T; Elsabbagh, M; Johnson, M; Singh, I (Wiley, 2021)
Background Since the 1990s, increasing research has been devoted to the identification of biomarkers for autism to help attain more objective diagnosis; enable early prediction of prognosis; and guide individualized intervention options. Early studies focused on the identification of genetic variants associated with autism, but more recently, research has expanded to investigate neurodevelopmental markers. While ethicists have extensively discussed issues around advances in autism genomics, much less ethical scrutiny has focused on research on early neurodevelopment and on the interventions being developed as a result.